Pengaruh Induksi Tukak Lambung Menggunakan Aspirin terhadap Kerusakan Jaringan Mukosa Lambung Mencit - Widya Vergiana Oktrinorma; Niken Indriyanti; Nur Masyithah Z (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Gastric ulcer is a condition of damage to the gastric mucosa accompanied by an inflammatory process. Gastric mucosal damage can be induced by various factors, one of which is non-steroidal anti-inflammatory drugs (NSAIDs). The purpose of this study was to assess the appropriate dose and time as a cause of damage to the gastric mucosa of mice due to exposure to aspirin. Before being induced, mice were fasted for 24 hours, white mice DDY strains (Deutschland, Denkenand and Yoken) were divided into 3 groups namely normal groups, aspirin 14 mg / 20 g BW (1 day), aspirin 14 mg / 20 g BW (2 days) orally. The results showed that the aspirin induced group 14mg / 20g BW had the most significant weight loss of mice, and showed the most severe epithelial tissue damage to the gastric mucosa with mucosal integrity score based on Barthel Manja criteria, namely 1. It can be concluded that the right dose of aspirin as an induction of damage to the gastric mucosa of mice is a dose of 14mg / 20 g BW (2 days).